2010
DOI: 10.1002/cjce.20283
|View full text |Cite
|
Sign up to set email alerts
|

Polymer aids for settling and filtration of oil sands tailings

Abstract: Commercial Magnafloc 1011 (Percol 727) polymer and in-house synthesised Al-PAM polymer were used to flocculate oil sands tailings that were derived from low and high fines oil sands ores. Fines are defined as mineral solids less than 44 m. The performance of polymers was evaluated in terms of tailings settling, filtration rate, and final moisture content of tilter cakes. Both polymers were shown to effectively flocculate the derived oil sands tailings and hence to enhance tailings settling. Al-PAM performed ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 9 publications
(20 reference statements)
0
40
0
Order By: Relevance
“…The above data was obtained from the filtration of oil sands tailings treated with different flocculants. Reproduced with permission . Copyright 2010, John Wiley & Sons.…”
Section: Performance Assessment Of Flocculantsmentioning
confidence: 99%
“…The above data was obtained from the filtration of oil sands tailings treated with different flocculants. Reproduced with permission . Copyright 2010, John Wiley & Sons.…”
Section: Performance Assessment Of Flocculantsmentioning
confidence: 99%
“…To effectively filter fines-rich feed, either: a) cake thickness must be controlled and minimized (Lockhart & Veal, 1996), or b) particles will need to be coagulated and/or flocculated to promote their effective size and reduce resistance to filtration. The latter approach has seen an increasing number of experimental work and applications in treating fine coal tailings (Alam, et al, 2011), red mud , and oil sand tailings (Xu, et al, 2008;Alamgir, et al, 2012;Wang, et al, 2010), although polymer dosage control is critical for final cake moisture when flocculants are used (Lockhart & Veal, 1996). Surfactants can also be applied at proper dosages to render the particles hydrophobic and hence increase the recession rate of water from the filter cake (Stroh & Stahl, 1990;Morey, 2013).…”
Section: Filtration and Electrofiltrationmentioning
confidence: 99%
“…As a result, large filtration areas are required to accommodate high-rate processing plants. Laboratory investigations on the pressure filtration of oil sands MFT revealed that higher throughputs can be achieved by proper fine solids flocculation and the selection of a two-stage filtration process (Wang, et al, 2010;Alamgir, et al, 2012). Figure 7 compares single stage filtration (plain region) and two-stage filtration (i.e.…”
Section: Filtrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many efforts involving physical, chemical, and biological means have been made to consolidate and enable the reclamation of fluid from tailings (Li et al, 2003;Matthews et al, 2002;Mpofu et al, 2004;Proskin et al, 2010;Sworska et al, 2000;Wang et al, 2010). However, the present technologies are environmentally unfriendly or economically unfeasible.…”
Section: Introductionmentioning
confidence: 97%